ICT IN PHYSICS CLASSES - Soyibnazarov Abbosjon Ikromjonovich (Scholars Digest Publishing, 2023)
In this article, the relevance of the use of information technologies and the possibilities of networks are confirmed by the strategic directions of the development of education in our country. An overview of the continuous use of ICT in physics classes, the need to regularly update several interrelated elements to ensure a high-quality level of education, and new educational technologies is held.
Keywords: Physics, ICT, computerization, interactivity, multimedia, modeling, communication, illustrative, visual.